The Role of Human Resource Management to Increase Competitiveness - Riskiana, Hilda; Putri Meliana Santoso; M. Prayoga Budi Santoso; Iriani Ismail (PT FORMOSA CENDEKIA GLOBAL, 2024)
Human resource management has a major role in increasing the competitiveness of Micro, Small and Medium Enterprises (MSMEs). The level of competitiveness of MSMEs is very dependent on the ability of human resources to manage, advance and empower the workforce. The aim of this research is to identify the contribution of human resource management in increasing the competitiveness of MSMEs. This research uses descriptive qualitative methods and focuses on the Basecamp Café in Bangkalan as the research location. The results of data collection show that human resource management has a crucial role in forming quality employees with optimal performance at Café Basecamp. This creates advantages for human resources in the cafe to contribute to achieving the cafe's vision and mission. To increase competitiveness, it is important to pay attention to the quality and competence of human resources by managing them through training, so that human resource management can be done effectively and efficiently